PENGEMBANGAN MODEL SISTEM BERBASIS PENGETAHUAN PADA LEMBAGA KONSULTASI MANAJEMEN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Faiza Renaldi; Tacbir Hendro Pudjiantoro; Aceng Nursamsudin (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Management Consulting Institute (MCI) has the aim to assist SME (Small and Medium Enterprise) entrepreneurs in realizing their goals through their business activities. The final product provided by the MCI is suggestion of documents that must be done by the company in dealing with their problems. Of course, the processes are given through a stage of preliminary observations by collecting initial data and compared with the issues (problems) happened inside the company.In this study, we will develop a Knowledge-Based Systems that stores information in the form of reports from the consultation process between the MCI and SMEs. The system allows users (consultants within MCIs) to access a collection of knowledge and pick the most (or a set of) relevant knowledge (according to industry type, the type of problem, etc.) to be used in subsequent consultations. Also, there is a non-supervised learning facility to calculate the correlation between the documents with references available.This research uses case studies and report data on the projects Micro, Small and Medium Enterprises (SMEs) owned by MCI. Taking a case study on SMEs for Knowledge-Based Systems has the most important goal to reduce the burden of the cost during the preliminary observations which will lower the total cost will be charged to SMEs in the use of MCI services. Keywords: Knowledge-Based Systems, Excavation Text, Not supervised Learning, MSME, Institute of Management Consultancy